2016
DOI: 10.1007/s00270-016-1414-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Embolization with a Mixture of Absolute Ethanol and Iodized Oil for Poorly Visualized Endophytic Renal Masses Prior to CT-Guided Percutaneous Cryoablation

Abstract: TAE using a mixture of absolute ethanol and iodized oil to improve visualization of endophytic renal masses facilitated tumor localization on unenhanced CT, permitting depiction of the tumor edge as well as a safe margin for ablation during CT-guided PCA, with an acceptable decline in renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Patients with an insufficient follow up of <6 months and those who underwent PCA for recurrent tumors after cryoablation were excluded; the remaining 73 patients formed the study population. PCA was carried out using an argon‐based cryoablation system (CRYO‐HIT; Galil Medical, Yokneam, Israel), as previously described …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with an insufficient follow up of <6 months and those who underwent PCA for recurrent tumors after cryoablation were excluded; the remaining 73 patients formed the study population. PCA was carried out using an argon‐based cryoablation system (CRYO‐HIT; Galil Medical, Yokneam, Israel), as previously described …”
mentioning
confidence: 99%
“…PCA was carried out using an argon-based cryoablation system (CRYO-HIT; Galil Medical, Yokneam, Israel), as previously described. 4,5 Renal functional outcome was assessed by eGFR, calculated using the Modification of Diet in Renal Disease equation. 6 The percentage of eGFR was calculated in the same manner (%eGFR, postoperative eGFR / preoperative eGFR 9 100).…”
mentioning
confidence: 99%
“…Michimoto et al. reported that the use of TAE with ethanol and iodized oil permitted visualization of an endophytic tumor with a safe margin for ice ball formation on unenhanced CT [9] . Using a mixture of 5 parts of absolute ethanol and 2 parts of iodized oil, we could visualize and safely puncture our patient's large and hypervascular tumor.…”
Section: Discussionmentioning
confidence: 99%
“…PCA for stage T1a or T1b RCC has demonstrated a high local control rate [10] . This technique allows clear visualization of the ablated area to avoid incomplete ablation and injury of adjacent organs [9] . Combined with TAE and hydrodissection to prevent complications, PCA was a safe and feasible treatment for stage T1b RCC in the HK of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Before administration, NBCA requires to be mixed with Lipiodol ® to make it radiopaque and to delay its polymerisation rate. The combination with Lipiodol ® also offers the potential benefit of enhancing tumor localization during CT-guided ablation [ 32 , 36 , 37 ], that could be particulalry useful in settings of poorly visualized endophytic renal tumor [ 37 ], or in patients with compromised renal function for whom contrast medium injection should be reduced.…”
Section: Introductionmentioning
confidence: 99%